IKA-FLOW : A Flexible Body Overset Mesh Implementation for Fish Swimming - Coe, Michael; Gutschmidt, Stefanie (OpenFOAM® Journal, 2023)
Simulation of inertial aquatic swimmers requires fluid structure interactions with temporal body geometry deformation. In practice, his results in a change of the computational domain boundaries that represent the ”swimmer.” These simulations are traditionally done sing body-fitted mesh and mesh morphing methods, but have drawbacks of negative cell volumes and small time-steps to account for the complex swimming motion. In contrast, the overset mesh method, also provided by OpenFOAM®, overcomes most of the drawbacks of the mesh morphing method at the expense of interpolation error. The current OpenFOAM® overset motion library only supports rigid body motion and cannot be used to resolve a body undergoing undulation. A modified motion solver is presented that allows for the complex mesh motion of an overset mesh for four body-caudal fin (BCF) virtual swimmers. The results of this solver are compared with published data of body-fitted meshes. The effect of different simulation parameters (including number of solving iterations, time delay, and temporal resolution) is investigated. Additionally, a novel simulation and comparison of the Ostraciiform locomotion mode with Anguilliform, Carangiform, and Thunniform modes are made investigating the wake, drag and lift. It is concluded that fish undulation has a marked effect on reducing lift generation. Lastly, a comparison of turbulence models (Spalart-Allmaras, k − ω SST, and k − kL − ω) at multiple Reynolds numbers shows that all three models have similar performance at lower Reynolds numbers but diverge at higher numbers.